2019
DOI: 10.1002/mdp2.106
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the multiscale mechanical behavior of knitted textiles

Abstract: The nonlinear, anisotropic, and multiscale mechanical behavior of knitted textiles is investigated experimentally in this article. The approach is motivated by recent computational work by the authors that revealed, for the first time to their best knowledge, local‐global mechanical behavior effects related to the hierarchical, three‐dimensional structure of this type of materials. The investigation is carried out on single jersey knitted textile specimens. Mechanical testing consisting of tensile loading alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Previous researches have investigated the out-of-plane motion 19 but did not exceed a 5% strain range, whereas our work investigated these effects in a deformation range of up to 42%. Figure 12 shows out-of-plane displacement and form in tensile loading in structures a, b, and c. As mentioned in the experimental work, 37 a rapid transition of ordering in the loop geometry occurs up to stretching mode. This verifies that the modeling approach is sensitive enough to incorporate the complex mechanical behavior under in-plane load.
Figure 12.Side view of: (a) basic structure, (b) tie structure and, (c) adjusted structure at 18% deformation.
…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous researches have investigated the out-of-plane motion 19 but did not exceed a 5% strain range, whereas our work investigated these effects in a deformation range of up to 42%. Figure 12 shows out-of-plane displacement and form in tensile loading in structures a, b, and c. As mentioned in the experimental work, 37 a rapid transition of ordering in the loop geometry occurs up to stretching mode. This verifies that the modeling approach is sensitive enough to incorporate the complex mechanical behavior under in-plane load.
Figure 12.Side view of: (a) basic structure, (b) tie structure and, (c) adjusted structure at 18% deformation.
…”
Section: Resultsmentioning
confidence: 68%
“…It was demonstrated that this pathway in the wale direction appears to be less wavy, favoring yarn stretching and inter-yarn sliding over-rotation and out-of-plane motion. 37…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently water was applied which allowed the removal of the transfer paper's backing leaving the speckles on the surface. While there are many methods to transfer patterns onto a specimen including manual markers [53], micro stamps [54], lithography [55] and stencils [52], this method was chosen for ease of use and good fidelity to pattern the speckles at the given length scales and printing parameters. Fig.…”
Section: Physical Experiments -Scalability and Error Analysismentioning
confidence: 99%
“…Our initial focus has been on representing fabrics that can be manufactured by weft-knitting machines consisting of two flat beds of needles and a single yarn. Since it has been shown that the structures formed by yarns and their interactions dominate the mechanical behavior of knitted textiles [2,3,4,5], TopoKnit represents these types of fabrics with yarns and the neighborhoods where they contact each other. The goal of our work is to define a low-level representation of knitted fabrics that has the properties of both completeness (i.e.…”
Section: Introductionmentioning
confidence: 99%